IbM Peternak Sapi Perah - Dwi Danesty Deccasari; Marli Marli; Hedher Tuakia (Jurnal ABM Mengabdi, 2014)
Government programs to manage local resources received from various parties , among others, in the world of banking , non-governmental organizations and business groups . One of the programs is the government's attention in order to save energy by making use of community resources , one of which is the use of waste cattle to replace kerosene or LPG substitute for everyday cooking. In rural areas Balesari Jambuwer District of Gunung Kawi Ngajum this is one area that has the advantage of dairy cows . Moreover in the area there is a milk processing plant Greenfield also supported geographic location is ideal for the breeding of dairy cows . The number of cattle in the area is quite high because of the obvious marketing milk distribution and the presence of banks and credit assistance Greenfied devoted to the procurement of cattle in the village Balesari . The development of this growing cattle in addition to an impact on the income of people increases also have a negative impact in the form of livestock waste that participate much . If this is allowed to pollute the environment and cause odor . To overcome this is to utilize the waste to substitute fuels LPG and kerosene prices have relatively more expensive . This waste can be processed into biogas which is very useful for day-to- day fuel . In devotion performed by the author in this Balesari village is to build three biogas dome for up to supply the necessary means or in other words to be used in the household . Our hope with the construction of the biogas will be able to infect other community members especially those living in rural Balesari Ngajum Subdistrict , Malang for both cattle utilizing waste .